2008
DOI: 10.1007/s10029-008-0376-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of paraduodenal hernias: mesh and mesh-less repairs. A report of four cases

Abstract: The mechanism of the herniation is thought to be a defective rotation of the superior mesenteric vein during embryonic development. Paraduodenal hernias are not high on the list of differentials for bowel obstruction. Some form of surgery is mandatory for all cases. The inferior mesenteric vein has to be sacrificed in some cases to facilitate reduction of the hernia contents. A mesh repair is reserved for large defects and recurrent hernias. Laparoscopic repair has been infrequently reported in the literature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 16 publications
2
81
0
Order By: Relevance
“…6 With the total number of reported cases in literature being less than 500 7 , the natural history is to remain asymptomatic during the lifetime of a person. 8 However, there is a 50 % lifetime risk of obstruction when a paraduodenal hernia is present. Clinically, most patients present with recurrent episodes of abdominal pain, often progressing to partial or complete intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…6 With the total number of reported cases in literature being less than 500 7 , the natural history is to remain asymptomatic during the lifetime of a person. 8 However, there is a 50 % lifetime risk of obstruction when a paraduodenal hernia is present. Clinically, most patients present with recurrent episodes of abdominal pain, often progressing to partial or complete intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The true incidences of these hernias are difficult to establish as many cases are either completely asymptomatic or misdiagnosed as functional gastrointestinal abnormalities. Only around 50% of paraduodenal hernias for example present with SBO or bowel strangulation 3 . In large autopsy series the prevalence of PDH has been reported Between 0.02 and 0.2% however it might be higher as suggested by a recent retrospective review of 294upper gastrointestinal X-ray series that revealed PDH in 2% of the reviewed cases 4,5 .…”
Section: Discussionmentioning
confidence: 99%
“…75% of these hernias are left-sided and due to failed embryological development. The reported lifetime risk of obstruction and bowel strangulation is around 50% with a mortality of 20% and higher 2,3 . The diagnosis of PDH is difficult as symptoms are often nonspecific and many clinicians are unfamiliar with this rare condition.…”
Section: Introductionmentioning
confidence: 99%
“…Even though all of the studies are of low LE, the potential role of laparoscopy in the diagnosis seems to be demonstrated in them and would, at times, prevent unnecessary laparotomies [298][299][300][301][302][303][304][305][306][307][308][309][310][311][312][313][314][315][316][317].…”
Section: Incarcerated/strangulated Herniasmentioning
confidence: 99%